2001
DOI: 10.1001/jama.286.19.2437
|View full text |Cite
|
Sign up to set email alerts
|

Oculopharyngeal Muscular Dystrophy in Hispanic New Mexicans

Abstract: Individuals in this cohort had clinical and genetic characteristics of classic OPMD. Longevity was not affected, but patients experienced considerable morbidity. The origin of the PABP2 mutation in New Mexican OPMD patients is unclear, although the geographic and genetic isolation of northern New Mexicans with a long ancestry in this region may have contributed to the development of this cohort. This disease cohort represents a large and previously unrecognized health care issue in the state of New Mexico and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 39 publications
4
53
1
Order By: Relevance
“…Brais et al, reported mean ages of 48.1 and 50.7 years for ptosis and dysphagia respectively in a cohort of French-Canadians with a (GCN) 13 mutation, which is consistent with a study in a cohort of Hispanic New Mexican cases with dominant OPMD and mean age of onset of 52 and 54 for ptosis and dysphagia 3,8 . However, the severity of the dominant OPMD phenotype is variable and severe cases with symptoms of ptosis and dysphagia before 45 years of age and incapacitating proximal leg weakness before 60 years of age represent 5 to 10% of all cases.…”
Section: Figure 1: (A) Pedigree Of the Oculopharyngeal Muscular Dystrsupporting
confidence: 71%
“…Brais et al, reported mean ages of 48.1 and 50.7 years for ptosis and dysphagia respectively in a cohort of French-Canadians with a (GCN) 13 mutation, which is consistent with a study in a cohort of Hispanic New Mexican cases with dominant OPMD and mean age of onset of 52 and 54 for ptosis and dysphagia 3,8 . However, the severity of the dominant OPMD phenotype is variable and severe cases with symptoms of ptosis and dysphagia before 45 years of age and incapacitating proximal leg weakness before 60 years of age represent 5 to 10% of all cases.…”
Section: Figure 1: (A) Pedigree Of the Oculopharyngeal Muscular Dystrsupporting
confidence: 71%
“…Two families [2,3] showed a perfect repeat, which contained (GCG) 10 . The patients of the other two families [1,4] did not show a perfect one, their repeat contained (GCG) 6 (GCA) 2 (GCG) 2 [17].…”
Section: S Muscle Biopsiesmentioning
confidence: 99%
“…André Barbeau found the largest cluster of OPMD in the Canadian Province of Quebec, with an estimated prevalence of 1:1,000 (Barbeau, 1966(Barbeau, , 1969Brais et al, 1995). Other large clusters have been observed in Bukhara Jews (1:600) (Blumen et al, 1997), Uruguayans (Medici et al, 1997), and Spanish Americans living in New Mexico (Becher et al, 2001) and California (Grewal et al, 1999). Cases of OPMD have now been reported in more than 30 countries.…”
mentioning
confidence: 99%
“…The disease has a slowly progressive course. Life expectancy is not diminished by the condition (Becher et al, 2001). Until recently, death occurred at an advanced age as a result of starvation or aspiration pneumonia.…”
mentioning
confidence: 99%